Imagetest: uma proposta de metodologia para aplicação de testes de software no domínio de transformações no espaço de cores - Dalcin, Sabrina Borba (2007)
This work is about the development of the ImageTest methodology which is dedicaded to applications that envelop transformations in the color space. This methodology describes the development and applications process of software tests, since the entrance of a participant in the team tests until the final application. This way, to emprove the test performances, the methodology aims the use of two techniques, both of them are in the bibliography, the structural and functional techniques. It has been used to the applications techniques the criterions all-of-us, equivalence partitioning, and boundary value analysis. Finally, the acceptance tests are done, which help the warranty that the software pleases the customer/user. So, the ImageTest can help the develoment and application of the cases of tests, aiming at the productivity increase and software quality, and the maintenance decrease.